The Dominant Physical Fitness of the Banda Aceh Dragon Boat Athlete 2020 - Sukardi Putra; Ifwandi Ifwandi; Maimun Nusufi; Amanda Syukriadi (Proceedings of AICS - Social Sciences, 2021)
Dragon Boat is a sport that requires the use of a long and narrow boat that must be paddled by human force using a paddle made of wood and fiber. Excellent physical components of the athlete and solid technique are both important in producing a good and fast boat speed. At the PORA Aceh event, the dragon boat athletes from Banda Aceh are always the winning team. However, because of the COVID-19 pandemic, athletes' training for the Aceh Pre-Pora in 2021 has been severely hampered. As a result, the goal of this research is to determine the level of dominant physical ability among Banda Aceh Dragon Boat athletes. The population in this study were all Banda Aceh Dragon Boat (PODSI) athletes which consisted of 24 athletes, namely 12 male athletes and 12 female athletes. Data analysis uses statistics in the form of calculating the average value and percentage. The results of the study found that: 1) the component of arm muscle strength was in the moderate category for females and males athletes. 2) the abdominal muscle endurance of female athletes is in the poor category and good category for males, 3) the arm muscle power component is in the good category for males, and females. Based on data analysis, it can be summarized that the overall dominant physical capacity of Banda Aceh Dragon Boat (PODSI) athletes in 2020 is in the moderate level category.Keywords: Evaluation, Dominant Physical Fitness, Dragon Boat.